2009
DOI: 10.1097/mrr.0b013e32830435b8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation of the Disability of Arm, Shoulder, and Hand questionnaire: Spanish for Puerto Rico Version

Abstract: The purpose of this study was to perform a cross-cultural adaptation of the Disability of Arm, Shoulder, and Hand (DASH) questionnaire to Spanish for Puerto Rico. Five steps were followed for the cross-cultural adaptation: forward translations into Spanish for Puerto Rico, synthesis of the translations, back translations into English, revision by an expert committee, and field test of the prefinal version. Psychometric characteristics of reliability and construct validity were evaluated for the final version. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…The pre-final version of the study also helped to identify some ambiguities found in the questionnaire. The content validity of the pre-final version was supported by the completeness of item responses, adequate score distri- [5]. A Cronbach's á value of 0.97 has been reported for the original DASH English version [4,5,6,8,12,13].…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The pre-final version of the study also helped to identify some ambiguities found in the questionnaire. The content validity of the pre-final version was supported by the completeness of item responses, adequate score distri- [5]. A Cronbach's á value of 0.97 has been reported for the original DASH English version [4,5,6,8,12,13].…”
Section: Resultsmentioning
confidence: 96%
“…The values obtained in this study were higher than the reported item-to-total correlations of the English version. Other versions of the DASH, for example, in the Cantonese Chinese version [15] the values ranged from 0.29 to 0.74; and for the Canadian French version [5] the values ranged from 0.27 to 0.88. This demonstrates that different countries have different values and therefore studies need to be done in countries with their own cultural groups in order to obtain normative data for that group and to find out the values specific to the country.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations